Case report: Severe asymptomatic hypertriglyceridemia associated with long-term low-dose rapamycin administration in a healthy middle-aged Labrador retriever - Evans, Jeremy B.; Chou, Lucy; Kaeberlein, Matt; Promislow, Daniel E.L.; Creevy, Kate E. (Frontiers in Veterinary Science, 2023)
Rapamycin is an mTOR inhibitor that has been shown to extend the lifespan of laboratory model organisms. In humans, rapamycin is used at higher doses as an immunosuppressive medication to prevent organ rejection. Numerous adverse effects are seen with rapamycin treatment in humans, with one of the most common being dysregulation of lipid metabolism. In humans, this often manifests as mild to moderate serum lipid elevations, with a small subset developing extreme triglyceride elevations. This case report describes an 8-year-old, castrated male, clinically healthy Labrador retriever who developed severe hypertriglyceridemia associated with low-dose rapamycin administration over a six-month period. During this time, the dog was asymptomatic and displayed no other clinical abnormalities, aside from a progressive lipemia. Within 15 days of discontinuing rapamycin treatment, and with no targeted lipemic intervention, the dog's lipemia and hypertriglyceridemia completely resolved.